DNA barcoding of medaka fish Oryzias marmoratus in Lake Towuti, South Sulawesi, Indonesia - REZKI ASYA NUR; ANDI PARENRENGI; TUTY ARISURYANTI; HELMY WIDYASTUTI; IRMA ANDRIANI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Nur RA, Parenrengi A, Arisuryanti T, Widyastuti H, Andriani I. 2024. DNA barcoding of medaka fish Oryzias marmoratus in Lake Towuti, South Sulawesi, Indonesia. Biodiversitas 25: 3645-3652. Oryzias marmoratus (Aurich, 1935), an endemic species of Lake Towuti, the second-largest lake in Indonesia, is facing a critical situation. Its population in nature is near threatened, as per the IUCN, necessitating immediate molecular studies such as DNA barcoding techniques. These studies are crucial to prevent a decline in the population of O. marmoratus. DNA barcoding is not just a tool for identification, monitoring, and protection but a call for genetic conservation. Therefore, the research was intended to identify the genetic variation of medaka fish. O. marmoratus was collected in Lake Towuti, and for DNA barcoding using primers, the cytochrome oxidase subunit I (COI) gene. Medaka fish samples (n=8) were collected from fishermen. DNA was extracted, and nucleotides were sequenced using sequencing provider 1st Base. The sequences of DNA were analyzed using Bioedit, BLAST-N, Mega11, DnaSP, and Network programs to obtain a consensus sequence, haplotype diversity, nucleotide diversity, genetic distance, phylogenetic, and haplotype network. The result showed that in the BLAST-N analysis, eight samples were closely related to O. marmoratus (LC154797.1) (AP005981.1) (94,42-99,84% in similarity). Genetic variation indicated a high value with a detailed 0.983 haplotype diversity, 0.026 a low nucleotide diversity, and six haplotypes; genetic distance with an average of 0.025 and 0.079. Phylogenetic analysis established five clades. Information on intraspecies genetic variation of O. marmoratus in terms of genetics, especially in Lake Towuti, is needed for genetic conservation and as an animal model of biology and molecular studies.